Peran Komunitas Dalam Meningkatkan Literasi Dan Inklusi Keuangan Syariah - Galih Tegar Febrianto; Faza Ghulam Ahmad; Imamul Arifin (LPPM STAI Diniyah Pekanbaru, 2020)
Financial literacy and inclusion is a degree that shows how the public has understood and used financial products optimally. The reality shows that the level of literacy and financial inclusion in Indonesia is still at 38%. That means only 38 people out of 100 people can know and understand financial products well. On the other hand, the community has been known as a forum that unites communal Indonesians. Here the community is become a mediator and accelerates the increase in financial literacy and inclusion. Potential owned by the community at least include (1) helping to sustain the National Strategy on Financial Literacy in Indonesia; (2) mediators for the development of Islamic financial literacy and inclusion through social capital; and (3) open cooperation with participatory culture